Sistem Kepemimpinan Holokratis: Menghilangkan Hirarki Tradisional untuk Efisiensi SDM di Startup: (Fokus: Bagaimana peran HR berubah ketika perusahaan tidak lagi memiliki manajer konvensional) - Faqihul Mukoddam; Ibnu Athoillah; Wira Adrina; Mochammad Isa Anshori (CV. Aksara Global Akademia, 2026)
The adoption of holocratic leadership systems has become a crucial strategy for startups navigating market volatility, which demands organizational agility through the elimination of traditional hierarchies. This study aims to analyze the transformation of the Human Resource (HR) department's role within holocratic systems and its impact on HR efficiency in startup environments. Employing an integrative literature review approach, this research synthesizes various findings from reputable global and national journals published within the last five years to map the shifts in managerial functions. The results indicate that in structures devoid of conventional managers, the HR role transforms from a controlling authority into a system architect and governance facilitator that maintains compliance with the organizational constitution. HR efficiency is achieved through clear authority distribution within dynamic roles, transparent peer-to-peer feedback mechanisms, and the removal of slow bureaucratic coordination costs. The contribution of this research lies in the formulation of the